Unlocking the global commons: legal analysis of benefit-sharing for marine genetic resources in the BBNJ agreement - Steel Rometius; Wei Wang; Wei Wang (Frontiers in Marine Science)
The Biodiversity Beyond National Jurisdiction (BBNJ) Agreement marks a significant step in governing global commons, yet faces implementation challenges regarding marine genetic resources (MGRs). Key limitations include ambiguous definitions of derivatives, tension between freedom of high seas and common heritage principles, and uncertain benefit-sharing models. In response, this paper proposes three improvements: (1) expanding MGRs interpretation under the Vienna Convention to include derivatives, accompanied by a clarifying negative list; (2) implementing a phased benefit-sharing mechanism that progressively incorporates common heritage principles as MGRs approach commercialization; and (3) developing a hybrid model combining monetary and non-monetary contributions with minimum standards to ensure benefits for developing States. These solutions would enhance marine biodiversity protection while ensuring equitable distribution of MGR benefits.